Effect of critical micelle concentration of imidazole ionic liquids in aqueous solutions on the wettability of anthracite. (15th January 2022) - Wang, Hui; Xie, Jingna; Xie, Jun; Jiang, Hehe; Wen, Yongzan; Huang, Wanpeng; Wang, Gang; Jiang, Bingyou; Zhang, Chao
Abstract: In this study, the influence of ionic liquids (ILs) on the microstructure and wetting behaviour of anthracite is explored. 1 H NMR and conductometry are used to determine the critical micelle concentration (CMC) for the aggregation of the ILs in an aqueous solution. XPS and zeta potential are used to analyse the changes in functional groups on the surface of coal treated with ILs and their effects on the wetting process. The results show that with an increase in the concentration of the ILs, the chemical shift of the end proton of the alkyl side chain moves forward to the high field, and the chemical shift value decreases. 1-Butyl-3-methylimidazolium chloride [Bmim][Cl] and 1-butyl-3-methylimidazolium tetrafluoroborate [Bmim][BF4 ] in aqueous solution attain the CMC at 0.93 mol/L and 0.95 mol/L, respectively. XPS results show that at the CMC of [Bmim][Cl], the relative content of oxygen-containing functional groups (C–O―, CO, COO―) is higher, and the wetting effect is better. When the concentration of [Bmim][BF4 ] in aqueous solution is 0.5 mol/L, it has a low hydrophobic group (C–C/C–H) content and strong wetting ability to coal dust. At the CMC, [Bmim][Cl] aqueous solution has an inhibiting effect on the wetting behaviour, while [Bmim][BF4 ] has the opposite effect. Graphical abstract: Image 1 Highlights: [Bmim][Cl] and [Bmim][BF4 ] formed micelles at 0.93 mol/L and 0.95 mol/L. The change in functional group structure of anthracite treated with ionic liquids. Explanation of the wetting action of ionic liquids before critical micelle formation.